Development and Approval of a Multidimensional Model of the Clinical Effectiveness of Treatment Technologies for Patients With a Mild COVID-19 Associated With Comorbidities - Yakovenko, Oleh; Soloviov, Serhii; Smetiukh, Mykhailo; Khanin, Oleksandr; Khodosh, Eduard; Dziublyk, Yaroslav; Surtaieva, Nataliia (Innovative Biosystems and Bioengineering, 2024)
Background. Today’s latest infection, COVID-19, remains an urgent problem of the Ukrainian healthcare system, which requires further efforts to develop effective treatment strategies, especially considering the potential exacerbation of comorbidities. Objective. Develop and approve a multivariate model of the effectiveness of the treating mild COVID-19 in patients with comorbidities, using Aminocaproic acid in comparison to nirmatrelvir/ritonavir and symptomatic therapy as examples. Methods. The modeling was based on the results of a clinical study involving three groups of patients with mild COVID-19. Clinical symptoms and quality of life were dynamically evaluated through standardized questionnaires. Regression analysis was used to analyze the dynamics of clinical symptoms and identify general patterns and their correlation with quality of life. Results. Modeling the dynamics of individual clinical symptoms allowed for the examination of recovery trends in mild COVID-19 patients under different drug treatments. Aminocaproic acid demonstrated a faster alleviation of primary respiratory symptoms compared to alternative treatments. Regression analysis highlighted that cough, sore throat, and general fatigue exert the most significant negative impact on the quality of life. These symptoms contribute to the decline in both physical and psychological health and limit activity during the disease course. Conclusions. This study presents a novel, multidimensional model considering both the dynamics of individual clinical symptoms and patients’ quality of life. The developed model was validated with retrospective data from mild COVID-19 patients with comorbidities. A multidimensional simulation of the clinical effectiveness of the use of aminocaproic acid, nirmatrelvir/ritonavir, or symptomatic treatment supports the preferential use of aminocaproic acid over other treatment methods. The quality-of-life modeling has enhanced our systematic understanding of the interplay between a set of clinical symptoms and overall patient condition, providing a rational foundation for treatment and care decisions.